Patient suffering from lichen sclerosus together with partial labial fusion (adhesion) and inflammatory infection of the vulva, vagina and anal area - Grażyna Jarząbek-Bielecka; Małgorzata Mizgier; Jacek Boroch; Magdalena Pisarska-Krawczyk; Mariola Pawlaczyk; Ewa Jakubek; Witold Kędzia (IMR Press, 2020)
The etiology of lichen sclerosus is not fully known, due to its chronic and progressive nature. The predisposing factor is physiological hypoestrogenism, hence the condition concerns girls during their developmental phase considered as estrogen silent (even as early as at the age of 6 months). The paper presents a 5-year-old patient coming from a rural area and suffering from lichen sclerosus together with partial labial fusion (adhesion) and inflammatory infection of the vulva, vagina and anal area. These symptoms intensified after antibiotic therapy the girl had undergone due to a respiratory tract infection. There were changes in the skin of the labia majora and buttocks indicating lichen sclerosus - swelling, traces of scratches, secondary redness, partial fusion of the labia minora on the side of the crotch known as the fourchette, and a runny yellow-white discharge from the vagina.